Tabungan Idul Fitri Sebagai Salah Satu Produk Simpanan Di BMT UGT Sidogiri - Muhammad Syarofi ofy; Bisyarotul Walida (Airlangga Journal of Innovation Management, 2022)
Baitul Maal wat Tamwil (BMT) is a non-bank Islamic Financial Institution which has a familiar function, namely as a microfinance institution that is tasked with distributing funds as well as collecting funds from the public. One BMT function as a fund-raising medium is realized in savings products in form of Eid al-Fitr savings, where this savings is aimed at helping the community, especially those with middle to lower economic backgrounds, to ease them in fulfilling their needs of Eid al-Fitr moment. In those moment, muslim community usually spend more on visiting relatives during the holidays, food supplies for guests who come, and usual Eid al-Fitr envelope distributed to relatives and needy neighbors  as well as children of relatives who are used to getting a share every Eid al-Fitr moments. Eid al-Fitr savings has proven to improve the quality of the community's financial condition it facilitate of allocating a small amount of funds from the community for Eid al-Fitr needs so that it does not mixed with other daily needs. This savings is also able to educate the public about sharia contracts such as the mudharabah musyarakah contract used in Eid savings. This savings also benefits the Indonesian people who are predominantly Muslim who want to save their funds with sharia concepts. The existence of this research is expected to contribute in providing knowledge about Eid al-Fitr savings, can be a reference for further research, and be a consideration for the BMT in improving the mechanism of products and services in it so that it can maximize its role and helping the economy of small communities in Indonesia.